2018
DOI: 10.1021/acs.jpcb.8b02743
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of the CHARMM All-Atom Force Field for Ether Lipids and Model Linear Ethers

Abstract: Linear ethers such as polyethylene glycol have extensive industrial and medical applications. Additionally, phospholipids containing an ether linkage between the glycerol backbone and hydrophobic tails are prevalent in human red blood cells and nerve tissue. This study uses ab initio results to revise the CHARMM additive (C36) partial-charge and dihedral parameters for linear ethers and develop parameters for the ether-linked phospholipid 1,2-di- O-hexadecyl- sn-glycero-3-phosphocholine (DHPC). The new force f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 49 publications
5
41
0
Order By: Relevance
“…77 The ether oxygen and bonded carbon of the tail received charges consistent with the recently published linear ether FF, C36e. 78 In this study, it was found that reducing the C3 glycerol charge relative to QM results for linear ethers allows more water to penetrate the bilayer, improving agreement with the overall experimental surface area per lipid (based on F(q) crossing points). Because the glycerol linkage is branched rather than linear, borrowing partial charge from C36 results tuned specifically to the glycerol region of lipids is chemically consistent.…”
Section: Force Field Development and Validationsupporting
confidence: 62%
“…77 The ether oxygen and bonded carbon of the tail received charges consistent with the recently published linear ether FF, C36e. 78 In this study, it was found that reducing the C3 glycerol charge relative to QM results for linear ethers allows more water to penetrate the bilayer, improving agreement with the overall experimental surface area per lipid (based on F(q) crossing points). Because the glycerol linkage is branched rather than linear, borrowing partial charge from C36 results tuned specifically to the glycerol region of lipids is chemically consistent.…”
Section: Force Field Development and Validationsupporting
confidence: 62%
“…1). 3,10,11 However, as also shown in Figure 1, any deviation from the 12 Å cutoff in LJ leads to dramatic change in bilayer surface areas, and, as follows from the hexadecane results, surface tensions of alkane/air interfaces. This inconsistency was recognized in the original publication of C36, 1 but it was not possible to rectify the problem at that time because an efficient method for calculating long-range LJ interactions was not supported in CHARMM 12 and other major simulation programs.…”
Section: Introductionmentioning
confidence: 54%
“…1,2-dipropionyl-sn-glycero-3-phosphocholine C3-PC 3:0 3:0 1,2-dilauroyl-sn-glycero-3-phosphorylcholine DLPC 12:0 12:0 1,2-dimyristoyl-sn-glycero-3-phosphorylcholine DMPC 14:0 14:0 1,2-dipalmitoyl-sn-glycero-3-phosphocholine DPPC 16:0 16:0 1,2-dimyristoyl-sn-glycero-3-phospho-(1'-rac-glycerol) DMPG 14:0 14:0 DPPC is the linkage between the head group and tails, which can be parametrized separately as indicated by the parametrization of C36 lipid FF for ether lipids. 3 The second consideration is what properties should be covered in the training set. As commonly used benchmarks for lipid FF development, surface areas and membrane thicknesses were included.…”
Section: Lipids Covered and Nomenclaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] The CHARMM36 (C36) set has been especially successful. It covers many important lipid types 14,[18][19][20][21][22][23][24] and is well-validated for various properties such as bilayer areas, compressibilities, spontaneous curvature, and bending constants. 25 However, monolayer surface tensions from C36 substantially underestimate experiment, 14 as expected from the lack of long-range dispersion.…”
Section: Introductionmentioning
confidence: 99%